6-Chloro-1-({[(2E)-2-methyl-3-phenylprop-2-en-1-yl]oxy}methyl)-1,2,3,4-tetrahydroquinazoline-2,4-dione - Nasser R. El-Brollosy; Mohamed I. Attia; Ali A. El-Emam; Seik Weng Ng; Edward R. T. Tiekink (Acta Crystallographica Section E, 2012)
In the title compound, C19H17ClN2O3, the conformation about the ethylene bond [1.333 (2) Å] is E. The ten atoms comprising the quinazoline ring are essentially planar (r.m.s. deviation = 0.032 Å) and their mean plane forms a dihedral angle of 13.89 (7)° with the terminal phenyl ring; the molecule has an open conformation as these substituents are directed away from each other. In the crystal, centrosymmetrically related molecules are connected via N—H...O hydrogen bonds between the amide groups, leading to eight-membered {...HNCO}2 synthons. These are consolidated into a three-dimensional architecture by C—H...O, C—H...π and π–π interactions [ring centroid(N2C4)...centroid(C6) distance = 3.5820 (11) Å].